Ugi Reaction Followed by Intramolecular Diels–Alder Reaction and Elimination of HCl: One‐Pot Approach to Arene‐Fused Isoindolinones. Issue 30 (11th August 2017) - Huang, Jianjun; Du, Xiaochen; Van Hecke, Kristof; Van der Eycken, Erik V.; Pereshivko, Olga P.; Peshkov, Vsevolod A.
Abstract : A one‐pot procedure involving a four‐component Ugi reaction followed by an intramolecular Diels–Alder reaction/HCl elimination cascade has been developed to provide rapid access to the isoindolinone framework in a diversity‐oriented fashion. The scope of the process has been investigated with respect to all four components, and a comparison between the one‐pot and sequential approaches is given. The possibility of a late‐stage one‐pot functionalization through Suzuki coupling has been explored. Abstract : A one‐pot procedure involving a four‐component Ugi reaction followed by an intramolecular Diels–Alder reaction/HCl elimination cascade has been developed to provide rapid access to the isoindolinone framework in a diversity‐oriented fashion.